The Influence of Financial Literacy, Financial Technology, and Digital Marketing on Increasing MSME Income in The City of Surabaya - Winda Ayu Nindhya; Tituk Diah Widajantie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to test and prove the influence of financial literacy, financial technology, and digital marketing on increasing MSME income. The population in this research is MSMEs that have gone digital in the city of Surabaya. The sampling technique in this study used simple random sampling, totaling 98 respondents. The analysis technique used in this research is the Structural Equation Model (SEM) on a Partial Least Square (PLS) basis using Smart-PLS 4.0 software. The results of this research prove that financial literacy, financial technology, and digital marketing have a significant effect on increasing MSME income.